2015
DOI: 10.1016/j.ccell.2014.11.006
|View full text |Cite|
|
Sign up to set email alerts
|

Paradox-Breaking RAF Inhibitors that Also Target SRC Are Effective in Drug-Resistant BRAF Mutant Melanoma

Abstract: SummaryBRAF and MEK inhibitors are effective in BRAF mutant melanoma, but most patients eventually relapse with acquired resistance, and others present intrinsic resistance to these drugs. Resistance is often mediated by pathway reactivation through receptor tyrosine kinase (RTK)/SRC-family kinase (SFK) signaling or mutant NRAS, which drive paradoxical reactivation of the pathway. We describe pan-RAF inhibitors (CCT196969, CCT241161) that also inhibit SFKs. These compounds do not drive paradoxical pathway acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(103 citation statements)
references
References 39 publications
6
94
0
Order By: Relevance
“…They further concluded that these somatic mutations accounted for more cancer cases than either inherited genetic disease or specific environmental risk factors. These observations are also consistent with the idea that cancer is essentially a disease of “stemness” gone awry [7, 8]. …”
Section: Introductionsupporting
confidence: 88%
“…They further concluded that these somatic mutations accounted for more cancer cases than either inherited genetic disease or specific environmental risk factors. These observations are also consistent with the idea that cancer is essentially a disease of “stemness” gone awry [7, 8]. …”
Section: Introductionsupporting
confidence: 88%
“…Because CRAF signals as an obligatory dimer 50,65 , αC-OUT inhibitors fail to suppress its activity. Thus, αC-IN RAF inhibitors, by suppressing both BRAF and CRAF dimers can also be considered ‘pan-RAF inhibitors’ 66-68 and may be effective when used in combination in contexts such as RAS-mutant tumour cells, in which CRAF is known to be a major activator of ERK signalling downstream of RAS. However, a potentially narrow therapeutic window and allosteric priming (see below) are predicted to limit the effectiveness of αC-IN RAF inhibitor monotherapy in RAS-mutant tumours 30 .…”
Section: Models Of Raf Inhibitor Actionmentioning
confidence: 99%
“…CCT196969 and CCT241161 have been reported as dual pan-RAF and SRC kinase inhibitors 66 . Although crystallographic data are not available, these compounds behave biochemically in a similar manner to αC-IN RAF inhibitors.…”
Section: Development Of Raf Inhibitorsmentioning
confidence: 99%
“…Several BRAF inhibitors enhance BRAF dimerisation in a RAS-dependent manner thereby activating MAPK signalling [62]. Novel inhibitors are being developed to evade this phenomenon [69,70]. RAF dimers are functionally asymmetrical [71] with one RAF kinase functioning as an activator to stimulate activity of the second RAF kinase (receiver, Figure 3).…”
Section: Raf Dimerisationmentioning
confidence: 98%